Determinants of Dividend Policy and the Effect of Dividend Policy on Stock Price Volatility: A Comparative Study of Bombay Stock Exchange and National Stock Exchange - Raipancholia, Priyanka (2014)
This study aims to investigate the determinants of Dividend Policy and its effects on the Share Price Volatility in the Indian Stock Market. We do this by looking at the 30 most traded stocks on the Bombay Stock Exchange (BSE) and 50 most traded stock on the National Stock Exchange (NSE) for the period of 2004-2013. A Panel data approach is used and fixed effect regression is used for Determinants of dividend policy and Random Effects Model regression is run for the Share Price Volatility studies. In NSE the main determinants are Return on Assets, Size, Pattern of Dividends and Tax ratio. In BSE it is only Pattern of Dividends and Tax Ratio. Whereas for the price volatility regression, in NSE the dividends do not affect the Price volatility, rather the Size, Debt to Assets ratio, Earnings Retention Ratio are the most significant in explaining the stock price volatility. On the other hand, in BSE, Dividend Yield is a significant explanatory of changes in share price volatility, along with the same ratios that explained the NSE price volatility. Another important observation was that once the control variables are introduced in the share price volatility model the dividends don’t affect the NSE price volatility but it does in BSE. Also NSE seems to have better results in almost all the regressions models used. We also can connect the results to the Stock exchange characteristics and norms